2001
DOI: 10.1093/milmed/166.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Morbidity in the Australian Defence Force with Australian General Practice

Abstract: This study was designed to examine morbidity patterns among Australian Defence Forces members and to compare them with civilian general practice. The study was conducted in the outpatient departments of the Royal Australian Air Force (RAAF) No. 6 Hospital, Melbourne, Australia. The patients studied were male and female members of the RAAF (66%), Army (25%), and Navy (9%). The problems managed at all primary care consultations during 1993 and 1994 were coded using the Ninth Revision of the International Classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Athletic sports may increase the possibility of some lower-extremity disorders, and this might counteract the expected effect of physical activity on musculoskeletal health. A study on Australian Defence Force members found a high frequency of musculoskeletal problems, especially ankle, knee and spinal strains, among military personnel compared with a population in general practice [26]. Other studies have found high rates of military training-related injuries at or below the knee [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletic sports may increase the possibility of some lower-extremity disorders, and this might counteract the expected effect of physical activity on musculoskeletal health. A study on Australian Defence Force members found a high frequency of musculoskeletal problems, especially ankle, knee and spinal strains, among military personnel compared with a population in general practice [26]. Other studies have found high rates of military training-related injuries at or below the knee [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies conclude with a high prevalence of MSD among military personnel [22-24], and MSD are the most prevalent source of disability among United States Army soldiers and Navy personnel [21,25]. Several studies describe frequent musculoskeletal injuries caused by physical training among military personnel [26-29]. We could not find studies on the association between physical activity at work and at leisure and MSD among military personnel.…”
Section: Introductionmentioning
confidence: 90%
“…Individuals in the armed forces of all countries and military personnel are largely different from the ordinary individuals due to some physical tness and characteristics [1]. There are jobs with high levels of stress, including military jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Although epidemiologic large scale studies are scarce, data that exist from other countries indicate that military personnel have considerable psychiatric morbidity of varying magnitude, depending on the country and type of service. In addition, they suffer more intense work-related stress and more subclinical manifestations of dysphoria often attributed to the work environment [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%